Human-ignited fires result in more extreme fire behavior and ecosystem impacts - Stijn Hantson; Niels Andela; Michael L. Goulden; James T. Randerson (Nature Communications, 2022)
‘Human-caused fires and natural fires could have different impacts. Here the authors report a geospatial analysis of lightning-ignited and human-ignited fires in California between 2012 and 2018, finding that the latter were more likely to develop under extreme conditions with larger ecosystem impacts.’